2007
DOI: 10.1177/10634266070150030101
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and Emotional Problems Reported by Parents of Children Ages 6 to 16 in 31 Societies

Abstract: T his study compared parents' ratings of behavioral and emotional problems on the Child Behavior Checklist (Achenbach, 1991;Achenbach & Rescorla, 2001) for general population samples of children ages 6 to 16 from 31 societies (N = 55,508). Effect sizes for society ranged from .03 to .14. Effect sizes for gender were ≤ .01, with girls generally scoring higher on Internalizing problems and boys generally scoring higher on Externalizing problems. Effect sizes for age were ≤ .01 and varied across types of problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

56
269
9
20

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 323 publications
(354 citation statements)
references
References 28 publications
56
269
9
20
Order By: Relevance
“…The prevalence in the present population 11 was in line with Scandinavian findings [22][23][24][25] and fairly low compared to other preschool studies in the US. [6][7][8][9][10] Thus, to increase the generalizability of our results, we will determine screening efficiencies for the most common range of prevalences.…”
supporting
confidence: 91%
“…The prevalence in the present population 11 was in line with Scandinavian findings [22][23][24][25] and fairly low compared to other preschool studies in the US. [6][7][8][9][10] Thus, to increase the generalizability of our results, we will determine screening efficiencies for the most common range of prevalences.…”
supporting
confidence: 91%
“…Results were in line with prior studies that identified intensity and type of children's behavior problems to be related to their age (Jaser et al 2005), sex (Rescorla et al 2007), maternal level of psychological distress (Frye and Garber 2005) and perception of security to both parents (Rakow et al 2011). Various studies stated that boys tended to display more externalized behaviors (Rescorla et al, 2007) as found in the present study (main scale and both delinquent and aggressive behaviors), being more withdrawn, having more social and attention problems.…”
Section: Discussionsupporting
confidence: 92%
“…Various studies stated that boys tended to display more externalized behaviors (Rescorla et al, 2007) as found in the present study (main scale and both delinquent and aggressive behaviors), being more withdrawn, having more social and attention problems. Findings from a review by Romano and De Luca (2001) on the impact of CSA among boys and girls on later psychological functioning suggested that in comparison to girls, boys were likely to experience more episodes of abuse and more violent CSA.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…The YSR consists of 112 items using a 3-point Likert scale, with higher scores indicating more mental health problems. The YSR has demonstrated reliability and validity across various populations including Korea as well as Western countries Rescorla et al, 2007). Excellent Cronbach's alpha scores for the Total Problems scale (α = .93 -.95) have been established (Achenbach & Rescorla, 2001;Ebesutani et al, 2011;Ivanova et al, 2007;Rescorla et al, 2007).…”
Section: Mental Health Problemsmentioning
confidence: 99%